Development of the X-ROOT Learning Medium on Exponents in Grade VIII - Rahmah, Nur Lailatul; Siti, Faridah (Jurnal Matematika, Statistika dan Komputasi, 2026)
This study aims to develop an X-ROOT mathematics learning medium for VIII-grade students on exponents. The research was motivated by the limited use of media in mathematics learning and students' difficulties in distinguishing multiplication from exponentiation and solving related problems. This study is Research and Development using the ADDIE model. Data were collected through observation, interviews, documentation, and questionnaires. The instruments included interview guidelines, observation sheets, and validation sheets. The subjects consisted of 21 students in class VIII B at Hasyim Asy'ari Islamic Junior High School in Malang City, chosen by the Purposive Sampling technique. The validity test was obtained from validation by a learning media expert and a material expert, while the practicality test was obtained from practitioner validation and student response questionnaires. The validity results showed scores of 86,6% from the media expert and 93,3% from the material expert. Practicality results were 90% from the practitioner and 93,3% from student responses. Based on these findings, the X-ROOT instructional media is categorized as very valid and very practical for mathematics learning.